Empathy in the Digital Age: The Role of Self-Control and Social Control in Addressing Cyberviolence - Irmayanti, Nur; Chusniyah, Tutut (Bisma The Journal of Counseling, 2024)
The increasingly advanced digital era, the phenomenon of cyber violence or digital violence is increasingly disturbing. This study aims to analyze the influence of self-control and social control (the role of parents and peers) on cyber violence. This study uses a quantitative approach, the sample consists of 250 high school students. Data analysis uses a structural transaction model (SEM). The results of the study showed a significant correlation between empathy and cyber violence, where individuals with low levels of empathy tend to engage in violent behavior online. Self-control is also significantly correlated with cyber violence; low levels of self-control are associated with detrimental behavior online. An interesting finding is the role of parents, where poor emotional relationships and lack of parental supervision contribute to cyber violence. No correlation was found between peer influence and cyber violence, indicating that social learning theory is stronger in the context of delinquent behavior with peers than cyber violence. Empathy also acts as a mediator between self-control and cyber violence, where high empathy strengthens the positive influence of self-control in avoiding detrimental behavior online. This study provides important insights for the prevention and control of cyber violence, emphasizing the importance of empathy, self-control, and the role of parents in shaping positive behavior in cyberspace.